Song as Media in Japanese Language Learning for Beginners - Launingtia, I Gusti Ayu Niken; Pramesti, Putu Dewi Merlyna Yuda (Vocational College of Diponegoro University, 2026)
This research aims to explore the effectiveness of using Japanese songs as a medium of learning to improve the mastery of knowledge and skills in the Japanese language among children at the beginner level. Considering the challenges faced by beginners in learning Japanese, including the complexity of the writing system and grammar, this research employs a qualitative approach with an action study design. The methods applied include direct observation, semi-structured interviews with learners and educators, and analysis of documentation related to learning activities. The results of the research indicate that the use of song media can not only create a fun and interactive learning atmosphere but also strengthen students' retention of understanding. Students reported an increase in motivation and confidence in speaking Japanese after participating in song-based learning. Observational data showed an increase in student participation, with many students actively involved in singing activities, which helped them to more easily remember understanding and sentence structures. The conclusion of this study emphasizes that the integration of song media in Japanese language learning significantly enhances the retention of integrity, pronunciation accuracy, and student engagement. Song media has been proven effective in supporting cognitive aspects, such as mastery of mathematics, as well as affective factors, such as motivation and self-confidence of learners. Therefore, it is recommended that educators choose songs that are appropriate for the students' level of understanding and combine them with other activities, such as lyric discussions and vocabulary exercises, to optimize the learning process.